Electrochemical reduction of CO2 on activated copper: Influence of surface area. (March 2020) - Giri, Sachin D.; Mahajani, Sanjay M.; Suresh, A.K.; Sarkar, A.
Graphical abstract: Highlights: Copper apparently becomes more active after reduction of copper oxides. Selectivity for formic acid formation increases after reduction of copper oxides. Increase in surface area of copper is 31 times higher after reduction. All oxides reduced back to copper within first few minutes of reduction. Abstract: In this work, we investigate the effect of activation (thermal or electrochemical) on the electrochemically active surface area (determined from under potential deposition of lead) and its influence on the electrochemical reduction of CO2 . The copper samples were characterized by XPS (X-ray photoelectron spectroscopy) and XRD (X-ray diffraction) before and after activation, and after performing electrochemical CO2 reduction experiments on them. The investigations suggest that the electrochemical reduction of CO2 takes place on metallic copper and the higher currents typically observed for activated copper is a manifestation of increased surface area. The specific method of oxidation does not seem to influence the electrochemical reduction of CO2, and only marginal differences compared to pristine copper were observed. Nonetheless, a definite change in selectivity of the reduction products was observed for activated copper foils compared to bare copper foil.